Operating Room to Post Anesthesia Care Unit: Introduction of a Standardized Checklist to Facilitate Patient Handoff - Purvis, John (My University, 2021)
The post anesthesia care unit is a dynamic environment and post-operative handoff reports are challenged by interruptions and time constraints. This can result in poor communication and the incomplete transfer of vital information which have the potential to harm patients. Poor or failed patient handoff reports have long been identified as potential sources of communication errors that may result in adverse patient outcomes. The purpose of this Doctor of Nursing Practice project was to assess anesthesia providers' and PACU nurses' perceptions of adequacy of the SBAR for Anesthesia Handoff Checklist. This quality improvement project was conducted at a large, Level I trauma center located in the southeastern United States. It utilized a pre- and post- survey design to complete a single Plan, Do, Study, Act cycle to assess user perceptions of a standardized handoff checklist among a nonrandomized convenience sample of CRNAs and PACU nurses who volunteered to participate in the project. Post-intervention survey responses to questions regarding ease of use, efficiency of organization, level of enthusiasm, and comprehensiveness of the SBAR for Anesthesia Handoff Checklist revealed that while perceptions of the checklist tended to be positive, participants were not overly enthusiastic.
Keywords: handoff, checklist, CRNA, PACU